2012
DOI: 10.4238/2012.september.17.1
|View full text |Cite
|
Sign up to set email alerts
|

Association of MHC class-III gene polymorphisms with ER-positive breast cancer in Chinese Han population

Abstract: ABSTRACT. Polymorphisms of the major histocompatibility complex (MHC) have been linked to many diseases, especially autoimmune disorders. Previous studies have shown that genetic variants in MHC class III are associated with breast cancer. To determine if there is an association between MHC class III and breast cancer risk in the Chinese Han population, we carried out a hospital-based case-control study in Guangdong and Jiangsu Provinces, including 216 histologically confirmed breast cancer patients and 216 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Epidemiology studies demonstrated association between Prrc2a SNPs and the risk of cancer, 44,45 rheumatoid arthritis, 46 insulin-dependent diabetes mellitus (IDDM) 47 , and obesity. 48 However, the roles of Prrc2a in the nervous system remained unknown despite its high expression in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiology studies demonstrated association between Prrc2a SNPs and the risk of cancer, 44,45 rheumatoid arthritis, 46 insulin-dependent diabetes mellitus (IDDM) 47 , and obesity. 48 However, the roles of Prrc2a in the nervous system remained unknown despite its high expression in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“… 4 PRRC2A has been defined as the increased risk of developing rheumatoid arthritis (RA), an auto-immune disease. 5 In addition, a single nucleotide polymorphism of PRRC2A was associated with ER-positive breast cancer, 6 lung cancer, 7 and non-Hodgkin lymphoma. 8 However, its expression profiles and molecular functions in HCC have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…PRRC2A is highly expressed in the hypothalamus, 30 which is involved with regulation of most endocrine organs, and mainly affects hypothalamic-pituitary-adrenal and hypothalamic-pituitarygonadal axes. 31 In addition, this gene has been reported to be associated with the age at menopause, 32 ER-and PR-positive breast cancer, 33 and type 1 diabetes mellitus, 34 indicating a role for PRRC2A in sex hormone regulation and immune inflammation. A predominance in women and a low risk of SLE development in prepubertal or postmenopausal women also suggest a role for estrogen in disease predisposition.…”
Section: Discussionmentioning
confidence: 99%